"أدوات التحليل المالي الحديثة ودورها في تقييم الأداء المالي للمؤسسة الاقتصادية " - سميرة, طرية; نورة, معروفي; زهور, زبيدي (University of eloued جامعة الوادي, 2021)
""تهدف هذه الدراسة إلى التعرف على أدوات التحليل المالي الحديثة المتمثلة في الأدوات الكمية والنوعية، ودورها في تقييم الأداء المالي للمؤسسة الاقتصادية وهذا بإسقاط الدراسة على مجمع صيدال خلال الفترة (2017 – 2019 )، وذلك بإستخدام أدوات التحليل المالي التقليدية، وإبراز العجز الذي توصلت إليه هذه الأدوات مع الإشاد بضرورة تطبيق أدوات التحليل المالي الحديثة في المؤسسة الاقتصادية لما تحققه من تطور للمؤسسة وسهولة تحقيق أهدافها المنشودة في أقرب وقت ممكن وبأقل تكلفة ممكنة وإضافة إلى ذلك إمكانية تقييم أسهم المجمع بالقيمة العادلة والتنبؤ بالمستقبل المالي للمجمع في المدى المتوسط والبعيد . كما وجدنا أن للمجمع القدرة على تمويل نفسه ذاتيا إذا تم إستخدام الأرباح المتحصل عليها بطريقة جيدة كما لا ننسى دور الشريك الخاص الوطني والأجنبي في تطور مجمع صيدال وإدخال عليه العديد من التكنولوجيات الجديدة . "" This study aims to identify the modem financial analysis tools represented in quantitative and qualitative tools, and their role in dividing the financial performance of the economic institution by dropping the study on SAIDAL Complex during the period (2017-2019), using traditionl financial analysis tools, and highlighting The deficit reached by these tools ,while commending the necessity of applying modern financial analysis tools in the economic institution due to the development they achieve for the institution and the ease of achieving its desired goals as soon as possible and at the lowest possible cost, in addition to the possibility of evaluating the shares of the complex at fair value and predicting the financial future of the complex In the medium and long term . We found that the complex has the ability to self-finance itself if the profits obtained are used in a good way, and we also do not forget the role of the national and foreign private partner in the development of the SAIDAL complex and the introduction of many new technologies to it . " "
مذكرة ماستر محاسبة
Keywords: أدوات التحليل المالي الحديثة – تقييم الأداء المالي – المؤسسة الاقتصادية; modem financial analysis tools - financial performance assessment - economic institution .